The influence of crude protein level in the basal diet on the determination of lysine requirements for broiler performance and part yields - TH Viola (Revista Brasileira de Ciência Avícola, 2009)
Amino acid requirements can be studied maintaining or not the ratio of the amino acids to lysine and changing or not dietary crude protein level. A third alternative was studied in this study conducted to evaluate broiler performance and weight gain of carcass parts, in response to increasing dietary digestible lysine (dig Lys) levels (0.70, 0.80, 0.90, 1.00, 1.055, 1.11, 1.165, and 1.22%). Two basal diets were formulated to contain 19.0% (diet A) and 20.5% (diet B) crude protein, and Met, Arg and Thr levels were formulated to maintain their ideal ratio to Lys. Three hundred and twenty CobbXCobb500 broilers, from 19 to 40 days of age, were used. Basal diet A was set for the 4 lowest levels of dig Lys, and diet B for the other four levels. Body weight (BW), weight gain (WG), feed intake, Lys intake, feed conversion (FC), carcass part weights and carcass, breast, leg, and thigh protein and fat were evaluated. Body weight, WG and Lys intake linearly increased with increasing dietary dig Lys, independently of basal diet CP content. A multiple regression effect was observed for FC, with the best estimated levels of dig Lys of 0.96% and 1.18% for diet A and B, respectively. Breast and carcass weight gain and breast protein and water gain showed multiple regression and split curves as a function of basal diet. The best responses were obtained with the highest crude protein level in the basal diet. Therefore, we concluded that high levels of crude protein in basal diets are recommended to study amino acid requirements for broilers.